2018
DOI: 10.1080/19331681.2018.1510355
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-discursive, mobilizing, emotional, and entertaining: identifying four successful communication styles of political actors on social media during the 2015 Swiss national elections

Abstract: Political actors are adapting their communication styles to the network media logic of social media platforms with varying success. This study investigates the communication styles used during the Swiss national election 2015 and their success in triggering digital reactions. In a quantitative content analysis of the "top 20" most reacted to messages on Facebook (n = 2170) and Twitter (N = 1796) of 246 Swiss parliamentarians and 11 parties we analyzed the impact of a pseudo-discursive, mobilizing, emotional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“…Hence, to grasp these less studied aspects, we apply Van Aelst and colleagues’ (2012) conceptualization that differentiates between two main dimensions of personalization: (1) Individualization means that instead of parties, individual politicians appear as central actors in the political arena; and (2) privatization means that politicians are presented as private individuals—their personal characteristics and lives are at the forefront of communication instead of their professional features. Interestingly, Keller and Kleinen-von Königslöw (2018) argue that in social media both dimensions are present as part of the entertaining political communication style; however, individualization is more common than privatization. Small (2016) also found that political leaders’ personalization strategies on Twitter primarily rely on individualization, while privatization is rather marginal.…”
Section: Visual Political Communication On Social Mediamentioning
confidence: 99%
“…Hence, to grasp these less studied aspects, we apply Van Aelst and colleagues’ (2012) conceptualization that differentiates between two main dimensions of personalization: (1) Individualization means that instead of parties, individual politicians appear as central actors in the political arena; and (2) privatization means that politicians are presented as private individuals—their personal characteristics and lives are at the forefront of communication instead of their professional features. Interestingly, Keller and Kleinen-von Königslöw (2018) argue that in social media both dimensions are present as part of the entertaining political communication style; however, individualization is more common than privatization. Small (2016) also found that political leaders’ personalization strategies on Twitter primarily rely on individualization, while privatization is rather marginal.…”
Section: Visual Political Communication On Social Mediamentioning
confidence: 99%
“…Social media have become an important channel through which political actors communicate with the voters and an arena for political participation in which citizens can respond to political messages (Keller & Kleinen-von Königslöw, 2018). On Facebook, these responses can take the form of "likes," "comments," "shares," and "reactions."…”
Section: Introductionmentioning
confidence: 99%
“…Based on the logic of virality (Klinger & Svensson, 2015), when users engage with content through any of the above means of interaction, political actors' posts are spread to wider audiences. The more interactions with a post, the more visible it becomes, not only to political actors' followers but also to their respective networks (Bene, 2017;Keller & Kleinen-von Königslöw, 2018). This increased visibility, in turn, has the potential to attract new voters (Bene, 2018), party members (Gibson et al, 2017), media attention (Bene, 2018;Chadwick, 2017), and even contribute to the electoral success (Bene, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has implications for the use of social media and how it influences politics (for example see Kim et al 2018;Keller andKleinen-von Königslöw 2018, Fitzi et al 2018). Our unique contribution is entrenched in how no previous study has looked at how Reddit influences behaviour.…”
Section: Consequences Of Outcomes Observed and Implications For Practicementioning
confidence: 92%